(untitled) (Human Factors in Design, 2023)
The study’s objective was to assess the knowledge and practices of healthcare professionals regarding the use of Assistive Technology with elderly patients in Palliative Care. It was a qualitative descriptive cross-sectional survey, using an open and semi-structured interview guide. The results indicate a patient-centered approach and individualized treatment plans for improving the quality of life in the palliative care process. The use of Assistive Technology as a care strategy proved to be effective, ensuring a humanized and tailored assistance to meet each patient’s needs.